Rocuronium versus Vecuronium for laparoscopic cholecystectomy - Tabdar, Sushila; Kadariya, Ekraj (Journal of Kathmandu Medical College, 2014)
Background: Laparoscopic cholecystectomy under general anaesthesia using Vecuronium is quite common these days. Some alarming complications like severe bradycardia and asystole after creation of carboperitoneum is not uncommon after its injection which is very stressful to both surgeons and anaesthesiologists. As an alternative, Rocuronium has been found safe in this regard till now used in many general anaesthesia requiring cases. So, it can be useful in laparoscopic cholecystectomy as well. Objective: To compare the haemodynamic, respiratory parameters and complications between Vecuronium and Rocuronium. Methods: In this randomised prospective double blind study conducted at Kathmandu Medical College from March 2013 to September 2013, a total of sixty patients of American Society of Anaesthesiologist (ASA) physical status I and II planned for laparoscopic cholecystectomy were randomly divided into two groups of thirty each by envelope method, with one group receiving Rocuronium and the other group receiving Vecuronium as muscle relaxants. Group A received injection Pethidine 1 mg/kg, Propofol 2.5 mg/kg and Vecuronium 0.1 mg/kg for induction. Group B received injection Pethidine 1 mg/kg, Propofol 2.5 mg/kg and Rocuronium 0.6 mg/kg for induction. After intubation the whole anaesthesia was maintained with oxygen, air, halothane and intermittent positive pressure ventilation. Intraoperative monitoring used were Pulse rate (PR), mean arterial pressure (MAP), arterial Oxygen saturation (SpO2), end tidal Carbondioxide (ETCO2), electro cardiography (ECG) and peripheral nerve stimulator (PNS). PR, MAP, SpO2, ETCO2, ECG were recorded before muscle relaxant, one minute after muscle relaxant, before intubation, one minute after intubation, before skin incision, one minute after skin incision, before carboperitonium, one minute after carboperitoneum, before extubation and one minute after extubation. Carboperitoneum if occurred any were also noted. Statistical analysis was done by using SPSS 19 verson. Student t test, Fisher’s exact test and Chi square test were used for the final analysis where P value <0.05 was considered significant. Result: Using Vecuronium as a muscle relaxant for laparoscopic cholecystectomy resulted in haemodynamic alteration intraoperatively by a significant reduction of PR one minute after carboperitoneum (62.80±11.25 versus 87.23±14.35 in Rocuronium group) where p<0.05. Bradycardia requiring Atropine was significant in vecuronium group with p<0.05. Conclusion: Rocuronium is less likely to cause bradycardia as compared to Vecuronium in laparoscopic cholecystectomy. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11776 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page: 190-195